2012
DOI: 10.1007/s00101-012-2055-8
|View full text |Cite
|
Sign up to set email alerts
|

Generation 55 +

Abstract: Generation 55 + is not asking for an upscaled position in hospitals. They expect respect and appreciation for their sound experience of work and life. Generation 55 + wants to be integrated and sought after. Keeping these employees fit, motivated and qualified is a sound approach to fight the foreseeable shortage of qualified staff in hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
2
0
1
Order By: Relevance
“…In terms of work-family conflict models, several participants from our study need to deal with the work-family-conflict type "overload", which reflects that the total demand on time is too great to meet the demands of different roles comfortably [43]. Just like in our study, several participants feel that they need to choose between private life or studies and not every medical student strives at all cost for her/his career [25,41,42,44]. A cross-sectional study from Germany suggested that more than onethird of medical students report not to have time to pursue individual interests [3].…”
Section: Effects Of Academic Studies On Private Life and Personal Chamentioning
confidence: 98%
“…In terms of work-family conflict models, several participants from our study need to deal with the work-family-conflict type "overload", which reflects that the total demand on time is too great to meet the demands of different roles comfortably [43]. Just like in our study, several participants feel that they need to choose between private life or studies and not every medical student strives at all cost for her/his career [25,41,42,44]. A cross-sectional study from Germany suggested that more than onethird of medical students report not to have time to pursue individual interests [3].…”
Section: Effects Of Academic Studies On Private Life and Personal Chamentioning
confidence: 98%
“…As in medicine as a whole, the hitherto rather male-dominated specialty is now also becoming more female 2 , 3 , 12 . It is recognised that issues involving the distribution of well-trained junior staff between the various specialties are becoming increasingly important 3 , 15 , 16 , 17 . The problem of shortage of doctors has caught up with not only the hospitals but also the outpatient services to a varying degree, depending on the region 16 , 18 , 19 .…”
Section: Discussionmentioning
confidence: 99%
“…Wie die gesamte Medizin wird auch das bislang eher männlich dominierte Fach nunmehr weiblicher 2 , 3 , 12 . Es ist bekannt, dass die Verteilungsproblematik des gut ausgebildeten Nachwuchses zwischen den einzelnen Fachbereichen an Bedeutung gewinnt 3 , 15 , 16 , 17 . Regionsabhängig unterschiedlich sind nicht nur die Krankenhäuser, sondern auch ambulante Strukturen in Bezug auf das Thema Ärztemangel eingeholt worden 16 , 18 , 19 .…”
Section: Diskussionunclassified